Circulating Leukotriene B4 Identifies Respiratory Complications after Trauma - Auner, Birgit (Hindawi Publishing Corporation, 2012)
Background. Leukotriene B4 (LTB4), a proinflammatory lipid mediator correlates well with the acute phase of Acute Respiratory Distress Syndrome (ARDS). Therefore, LTB4-levels were investigated to determine whether they might be a useful clinical marker in predicting pulmonary complications (PC) in multiply traumatized patients. Methods: Plasma levels of LTB4 were determined in 100 patients on admission (ED) and for five consecutive days (daily). Twenty healthy volunteers served as control. LTB4-levels were measured by ELISA. Thirty patients developed PC (pneumonia, respiratory failure, acute lung injury (ALI), ARDS, pulmonary embolism) and 70 had no PC (ØPC). Results. LTB4-levels in the PC-group [127.8 pg/mL, IQR: 104–200pg/ml] were significantly higher compared to the ØPC-group on admission [95.6 pg/mL, IQR: 55–143 pg/mL] or control-group [58.4 pg/mL, IQR: 36–108 pg/mL]. LTB4 continuously declined to basal levels from day 1 to 5 without differences between the groups. The cutoff to predict PC was calculated at 109.6 pg/mL (72% specificity, 67% sensitivity). LTB4 was not influenced by overall or chest injury severity, age, gender or massive transfusion. Patients with PC received mechanical ventilation for a significantly longer period of time, and had prolonged intensive care unit and overall hospital stay. Conclusion. High LTB4-levels indicate risk for PC development in multiply traumatized patients.